The effect of MXene on the mechanical and electromagnetic interference shielding features of carbon fabric/epoxy scalable laminated composites - Yuksel Yilmaz, Ayten Nur; Bedeloglu, Ayse Celik; Yunus, Doruk Erdem (Springer, 2025)
In this study, the aim was to improve the interfacial properties of carbon fabric-epoxy matrix composites using MXene, a 2D material with superior characteristics, as a reinforcement. To achieve this, carbon fabrics were first surface-activated using concentrated nitric acid, followed by spraying a solution containing MXene in varying weight percentages (0.2%, 0.4%, and 0.8%). Subsequently, epoxy matrix-based laminated composites were fabricated using the vacuum infusion method. The composites were then subjected to tensile, flexural, interlaminar shear strength (ILSS), Mode-I fracture toughness, and electromagnetic interference (EMI) shielding tests. The results showed that the composite reinforced with 0.4% MXene exhibited the highest mechanical performance, demonstrating increases of 12.71%, 12.63%, and 13.13% in flexural strength, ILSS, and tensile strength, respectively, compared to the reference carbon fabric-epoxy composite. Additionally, the Mode-I fracture toughness of this composite was improved by 25.32%. Scanning electron microscopy (SEM) analysis was conducted to examine the fracture regions of the composites and ascertain the underlying damage mechanisms. The increase in the amount of MXene coated on the fabric surface did not create a significant difference in the EMI-SE values of the composites in the X-band range. The total shielding effectiveness values of the CF, ACF, 0.2MX, 0.4MX, and 0.8MX samples were calculated as - 31.13 dB, - 31.39 dB, - 31.45 dB, - 32.77 dB, and - 32.63 dB, respectively. These findings demonstrate that MXene is an effective reinforcement for improving the interfacial properties of laminated composites for scalable production.
Keywords: Interlaminar Fracture-Toughness; Graphene Oxide; Electrophoretic Deposition; Surface Modification; Fiber Composites; Epoxy Composites; Nanocomposites; Nanotube; Woven; Enhancement